Pengaruh Pengelolaan Keuangan Daerah dan Sistem Akuntansi Keuangan Daerah terhadap Kinerja Keuangan Pemerintah: Studi Empiris pada OPD Provinsi Sumatera Barat - Tasya Aulia Syafdan; Fefri Indra Arza (Universitas Negeri Padang, 2024)
This study aims to analyse the influence of regional financial management and regional financial accounting system on government financial performance. The research was conducted at the West Sumatera Province Regional Apparatus Organization. The sampling technique uses purposive sampling. Method Data collection was carried out using a questionnaire. Regression analysis Multiple tests were carried out to test the hypothesis using SPSS 20 with results research shows that regional financial management has a positive effect on government financial performance while the regional financial accounting system does not has an influence on the government's financial performance.